2022
DOI: 10.12775/jehs.2022.12.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of botulinum toxin on improving quality of life in patients with chronic migraine

Abstract: Introduction and purpose: Migraine is a chronic condition affecting up to 10% of the adult population in Poland. Migraine pain is severe and may be accompanied by nausea or vomiting, as well as hypersensitivity to light, sounds or smells. Chronic form of migraine means the occurrence of headache a minimum of 15 days per month, for a period of at least three months, of which eight days or more of pain meet the criteria for migraine pain. The chronic form of migraine is targeted for treatment with botulinum toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study also showed that early initiation of botulinum neurotoxin therapy is more beneficial than treatment in the advanced phase of pain. [37][38][39][40][41][42]…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%
“…The study also showed that early initiation of botulinum neurotoxin therapy is more beneficial than treatment in the advanced phase of pain. [37][38][39][40][41][42]…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%